Peningkatan Pemahaman Iman Kristen Melalui Program Penyuluhan di Kalangan Siswa SMA dan SMK Yadika Soreang - Ferry Simanjuntak; Josef Christianto; Jeremy Mulyadi; Christopher Alexander (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Everyone needs to have a clear understanding of their faith. Likewise, a Christian needs to have a true understanding of the faith. That is why, this community service activity was carried out to increase understanding of the Christian faith through a discipleship program among Yadika Soreang High School and Vocational High School students, where for 7 (seven) days, some material was presented, such as the Guarantee of Salvation, Repentance, Jesus the Sole Ruler, Restoration of the Father's Heart, Self Image Restoration, Inner Wound Healing, Enjoying the Bible, the Life of Prayer, Love, Sex and Dating, Life Calls, Church History: The Early Church, Church History: Streams in Christianity, The Power of Words, and Religious Tolerance.